Unilateral biportal endoscopic lumbar interbody fusion versus minimally invasive transforaminal lumbar interbody fusion in the treatment of lumbar degenerative diseases: a retrospective multicenter cohort study - Xiang Chen; Jingbo Xie; Zhihui Zhang; Yi Liu; Liang Shi; Lang Hu (PLoS ONE, 2025)
Background Minimally invasive transforaminal lumbar interbody fusion (Mis-TLIF) is one of the most commonly used methods for lumbar fusion. However, in recent years, the unilateral biportal endoscopic lumbar interbody fusion (UBE-LIF) has also gradually attracted the attention of spine surgeons. This study aims to compare the perioperative and long-term clinical outcomes of the two procedures for lumbar degenerative diseases (LDD). Methods We collected clinical data of patients who had undergone minimally invasive transforaminal lumbar interbody fusion (Mis-TLIF) or unilateral biportal endoscopic lumbar interbody fusion (UBE-LIF) for lumbar degenerative diseases (LDD) from January 2019 to December 2022. The primary outcome measure was the Oswestry Disability Index (ODI) at 12 months postoperatively. Secondary outcome measures included 12-month visual analog scale (VAS) scores for low back pain (LBP) and leg pain (LP), and postoperative complication rate. Results There were no significant differences in the preoperative VAS scores for LBP, LP, or ODI between the two groups. The VAS score for LBP was significantly lower in the UBE-LIF group than in the Mis-TLIF group 1 week postoperatively (1.4 ± 1.1 vs. 2.1 ± 1.0, P = 0.001). However, there was no significant difference in the VAS scores for LBP, LP, and ODI at 1, 6, and 12 months postoperatively. The length of stay was significantly lower in the UBE-LIF than in the Mis-TLIF group (5.2 ± 1.1 vs. 6.3 ± 1.2 days, P < 0.001). The operative time (188.9 ± 19.8 vs. 159.5 ± 11.6 minutes, P < 0.001) of the UBE-LIF group was significantly higher than that of the Mis-TLIF group, while the estimated blood loss (131.0 ± 21.9 vs. 191.7 ± 23.3 ml, P < 0.001) and postoperative drainage volume (123.0 ± 55.4 vs. 191.2 ± 47.5 ml, P < 0.001) were significantly lower in the UBE-LIF than in the Mis-TLIF group. The complication rate was slightly higher in the UBE-LIF than in the Mis-TLIF group; however, the difference was not significant (11.5% vs. 5.0%, P = 0.299). Conclusion UBE-LIF can achieve better perioperative clinical outcomes than Mis-TLIF. However, in the long-term, these two procedures can achieve equivalent clinical efficacy.